2020
DOI: 10.1093/braincomms/fcaa024
|View full text |Cite
|
Sign up to set email alerts
|

Association of neuroinflammation with episodic memory: a [11C]PBR28 PET study in cognitively discordant twin pairs

Abstract: Alzheimer’s disease is associated with chronic response of innate immune system, referred as neuroinflammation. PET radioligands binding to the 18 kDa translocator protein are potential biomarkers of neuroinflammation. Translocator protein PET studies in mild cognitive impairment and Alzheimer’s disease have indicated controversial results, possibly reflecting interindividual variation and heterogeneity of study populations. We controlled for genetic and environmental effects by studying twin pairs discordant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The localization of inflammation matched the clinical syndrome (37) and correlated negatively with metabolism measured with 18 F-FDG PET (35)(36)(37). Furthermore, the degree of TSPO uptake correlated with worse cognition (33,38,39), better than the degree of amyloid deposition and, together with the degree of tau deposition, predicted the degree of cognitive worsening over 3 y (40). Inflammation correlated with white matter changes (41) and impaired large-scale functional connectivity on MRI (42).…”
Section: Neuroinflammation Pet In Neurodegenerative Disorders Alzheim...mentioning
confidence: 81%
“…The localization of inflammation matched the clinical syndrome (37) and correlated negatively with metabolism measured with 18 F-FDG PET (35)(36)(37). Furthermore, the degree of TSPO uptake correlated with worse cognition (33,38,39), better than the degree of amyloid deposition and, together with the degree of tau deposition, predicted the degree of cognitive worsening over 3 y (40). Inflammation correlated with white matter changes (41) and impaired large-scale functional connectivity on MRI (42).…”
Section: Neuroinflammation Pet In Neurodegenerative Disorders Alzheim...mentioning
confidence: 81%
“…Of course, it is not possible to draw conclusions from a case study of 1 twin pair, but interestingly, subsequent studies in cognitively discordant twin pairs from the older FTC study have confirmed lower glucose metabolism and smaller hippocampal volumes in co-twins with cognitive impairment compared with their co-twins without cognitive impairment ( Järvenpää et al 2004 ; Virta et al 2009 ). Notably, also an association between neuroinflammation and cognition has been found in cognitively discordant twin pairs ( Lindgren et al 2020 ).…”
Section: The Older Ftc Study—telephone Interviews In Screening Of Cog...mentioning
confidence: 99%
“…Two studies in Finnish twins have further looked at twin pairs discordant for episodic memory in relation to PET tracers measuring neuroinflammation ( Lindgren et al 2020 ) and amyloid pathology ( Lindgren et al 2021 ). These studies can inform if the associations between clinical and biological characteristics of AD are evident when controlling for shared genetic influences or alternatively implicate that these associations are mediated by genetic effects.…”
Section: The Older Ftc Study—telephone Interviews In Screening Of Cog...mentioning
confidence: 99%
See 1 more Smart Citation
“…The glial role in the innate immune system also involves general ‘sickness’ symptoms that shift an organism’s behavior to preserve energy at a time of high energy demand (Dantzer & Kelley, 2007; VanElzakker et al, 2019). However, long-term glial activation can disrupt the delicate symbiosis of glia, blood vessels, neurons, and cerebrospinal fluid in normal central nervous system function, and ongoing glial activation occurs in multiple neurological and neuropsychiatric conditions (VanElzakker et al, 2019) and is associated with symptoms that are commonly reported in PASC such as disrupted cognition (Barrientos et al, 2006; Lindgren et al, 2020), increased pain (Loggia et al, 2015), and other nonspecific symptoms of sickness.…”
Section: Introductionmentioning
confidence: 99%